2020
DOI: 10.3390/jcm9072134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pancreas Transplantation on the Patient Survival—An Analysis of the Japanese Pancreas Transplants Registry

Abstract: Background: The impact of pancreas transplantation, including kidney transplantation on patients’ life prognoses, is unclear in Japan. An analysis of the data of the Japan Pancreas Transplant Registry was performed to compare the patient survival between on the waiting list and after pancreas transplantation, and investigate the factors that affect the patient survival after pancreatic transplantation. Methods: The life prognoses of 361 patients who underwent pancreas transplantation from 2000 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…A future challenge is improving the outcomes of pancreas transplantation for older recipients with a long history of diabetes. As mentioned above, an older age and long history of diabetes were significant risk factors for a short‐term patient survival after pancreas transplantation in our previous study 12 . A reduction in waiting periods due to the increasing number of BDDs following the revision of the law is expected in the near future, but as this study showed, older patients with a long history of diabetes remain on the waiting list for pancreas transplantation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…A future challenge is improving the outcomes of pancreas transplantation for older recipients with a long history of diabetes. As mentioned above, an older age and long history of diabetes were significant risk factors for a short‐term patient survival after pancreas transplantation in our previous study 12 . A reduction in waiting periods due to the increasing number of BDDs following the revision of the law is expected in the near future, but as this study showed, older patients with a long history of diabetes remain on the waiting list for pancreas transplantation.…”
Section: Discussionmentioning
confidence: 48%
“…All patients who were candidates for pancreas transplantation were assessed by the committee of the Japan Society for Pancreas and Islet Transplantation. Recipient criteria were established and selection performed as previously reported 12 . In brief, the recipient criteria were as follows: A diabetic patient with renal failure.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the therapeutic effects of insulin on glucose metabolism, PTx can reduce diabetes-related complications, such as retinopathy, nephropathy, neuropathy, gastroparesis, and cardiovascular diseases. Furthermore, considering that the complications can lead to impaired quality of life and the occurrence of life-threatening events, the clinical benefit of PTx is evident for patients with diabetes mellitus 4 8 . However, the outcomes of PTx remain unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of normal glucose metabolism also has the secondary effect of potentially improving the life expectancy of PTx patients. 7,8 Since the first PTx was carried out at the University of Minnesota in 1966, PTx has now been carried out worldwide. 2,9 Posttransplant outcome is reportedly favorable.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in hemodialytic cases, simultaneous pancreas‐kidney transplantation (SPK) may alleviate the need for hemodialysis. Restoration of normal glucose metabolism also has the secondary effect of potentially improving the life expectancy of PTx patients 7,8 . Since the first PTx was carried out at the University of Minnesota in 1966, PTx has now been carried out worldwide 2,9 .…”
Section: Introductionmentioning
confidence: 99%